2007
DOI: 10.1094/cchem-84-4-0331
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Pharmaceutical Properties of Carboxymethyl Rice Starches Modified from Native Starches with Different Amylose Content

Abstract: Cereal Chem. 84(4):331-336Carboxymethyl rice starches (CMRS) were prepared from nine strains of native rice starches with amylose contents of 14.7-29.1%. The reaction was conducted at 50°C for 120 min using monochloroacetic acid as a reagent under alkaline conditions and 1-propanol as a solvent. After determining the degree of substitution (DS), the physicochemical properties including water solubility, pH, and viscosity of 1% (w/v) solution, scanning electron microscopy (SEM), and X-ray diffraction (XRD) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
2
10
1
Order By: Relevance
“…SEM of the native KL1 starch showed polygonal granules of 2 and 10 μm consistent with other rice starch granules and in agree- ment with a previous report (Kittipongpatana et al 2007). SEM image of CMRS prepared in this study showed no change compared with that of the native starch.…”
Section: Sem Analysis and X-ray Diffractionsupporting
confidence: 92%
See 2 more Smart Citations
“…SEM of the native KL1 starch showed polygonal granules of 2 and 10 μm consistent with other rice starch granules and in agree- ment with a previous report (Kittipongpatana et al 2007). SEM image of CMRS prepared in this study showed no change compared with that of the native starch.…”
Section: Sem Analysis and X-ray Diffractionsupporting
confidence: 92%
“…At 1% w/v concentration, the viscosity of CMRS prepared in this study (M-KL1) was higher than that of CMRS prepared using 1-propanol as the reaction solvent (N-KL1) in the previous report, emphasizing the effect of reaction solvent on the physicochemical properties of CMS (Tijsen et al 2001;Kittipongpatana et al 2007). M-KL1-2.5 showed a viscosity comparable to that of CMRS when tested at 1% w/v concentration, but increases 2.1-fold when compared at 3% w/v concentration.…”
Section: Viscositycontrasting
confidence: 52%
See 1 more Smart Citation
“…The procedure included repeated blendingfiltering step several times to maximize the yield and to eliminate soluble sugar (Mukprasirt & Sajjaanantakul, 2004). Jackfruit starch was then extracted from flour using a method modified from those described for isolation of jackfruit starch by Bobbio et al (1978) and for isolation of rice starch by Kittipongpatana, Chaitep, Kittipongpatana, Laenger, and Sriroth (2007). In brief, 600 mL of 0.05 mol/L NaOH was added into a 200-g portion of flour and stirred for 5 h at room temperature.…”
Section: Preparation Of Jackfruit Flour and Extraction Of Jackfruit Smentioning
confidence: 99%
“…The degree of substitution and the reaction efficiency were determined as described previously (Kittipongpatana et al, 2007;Wang et al, 2010).…”
Section: Preparation Of Carboxymethyl Jackfruit Starches (Cmjfs)mentioning
confidence: 99%